Pengakuan Hak Masyarakat Adat Mentawai Sebagai Penegakan Asas Kemanusiaan Warga Negara Indonesia - Siti Maizul Habibah (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2021)
The problem of indigenous peoples' rights continues to grow as well as the issue of the rights of the Mentawai indigenous peoples for that it is necessary to take some considerations into deciding policies. This study uses a literature study and the results show that there are still many problems related to the rights of indigenous peoples, especially regarding the recognition of the rights of the Mentawai indigenous peoples. Several considerations need to be used as a reference in making policies, one of which is related to humanity because indigenous peoples are part of Indonesian citizens.